(untitled) (International journal of medical sciences, 2026)
Acute Myocardial Infarction (AMI) remains a leading cause of in-hospital mortality worldwide, necessitating precise risk stratification to optimize therapeutic strategies. This article presents a prospective observational study conducted at the Department of Faculty Therapy of Andijan State Medical Institute. Using the IMRAD framework, the research investigates the prognostic determinants of the hospital course in 120 patients admitted with AMI. The study evaluates the predictive value of traditional scales such as GRACE and Killip, alongside novel metabolic markers including lipid peroxidation products and autonomic tone. The results demonstrate that while hemodynamic stability and time to reperfusion are primary prognosticators, the metabolic milieu characterized by oxidative stress and sympathetic overactivity significantly influences the development of early complications like arrhythmias and heart failure. The study concludes that a comprehensive prognostic model integrating clinical, instrumental, and metabolic parameters improves the accuracy of short-term outcome prediction in the local population.